The influence of organizational culture and motivation on employee performance at Banyan Tree Bintan - Tambunan, Susi Marta; Afni, Riza; Manurung, Rianto (Institute of Computer Science (IOCS), 2024)
Hotels are one of the destinations for tourists to rest before continuing their tourist destination. This is of course related to tourist satisfaction. The measure of tourist satisfaction is employee performance. Employee performance is also influenced by organizational culture and motivation. Organizational culture and motivation have a big influence in terms of improving performance. Based on this, this research was carried out with a sample of 80 people with questions using Likert scale measurements carried out using tests. This research instrument includes validity tests, reliability tests, multiple linear regression analysis. To test the classical assumptions, the normality test, multicollinearity test and heteroscedasticity test are used. To test the feasibility of the model, it includes the F test, R2 and t test using Excel and SPSS tools to obtain results that organizational culture and motivation influence employee performance both partially and simultaneously